The Effect of Profitability, Leverage, CPO Prices and Exchange Rates on Stock Prices (Study on Palm Oil Plantation Industry Sub-Sector Companies in 2018-2023) - Fauzan, Naufal Hilmy; Pertiwi, Tri Kartika (East Asian Journal of Multidisciplinary Research, 2025)
This study aims to analyze the impact of profitability, leverage, CPO price, and exchange rate on stock prices in palm oil plantation sub-sector companies listed on the Indonesia Stock Exchange during the 2018-2023 period. The study population includes companies in this sub-sector that were active on the Indonesia Stock Exchange during the same period. A purposive sampling method was used to select the sample, resulting in 13 companies that met the criteria, with a total of 78 observation data points over the six-year study period. The analysis technique applied is multiple linear regression using SPSS version 26 software. The study findings indicate that profitability positively influences stock prices, while leverage, CPO price, and exchange rates do not have a significant impact on stock prices.